Ferritic stainless steel and method for producing the same
Patent Information
- Application Number
- JP2023128815
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-08-07
- Publication Date
- 2025-02-20
AI Technical Summary
【0014】 本発明によれば、耐候性に優れるフェライト系ステンレス鋼材及びその製造方法を提供することができる。
Smart Images

Figure 2025024597000001 
Figure 2025024597000002 
Figure 2025024597000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a ferritic stainless steel material and a method for producing the same. [Background technology]
[0002] Ferritic stainless steel materials are inexpensive because they contain no Ni or only a small amount of Ni, but their applications are sometimes limited because they are inferior in corrosion resistance and workability to austenitic stainless steel materials.
[0003] In recent years, the expansion of applications of ferritic stainless steel materials has led to a demand for improved corrosion resistance of ferritic stainless steel materials. In particular, in applications such as building panels and piping, which may be used in outdoor environments (e.g., outdoor corrosive environments such as salt damage environments), weather resistance is required. Examples of weather resistance include the inhibition of rusting in outdoor environments and the inhibition of holes caused by corrosion.
[0004] As a technique for improving the corrosion resistance of ferritic stainless steel materials, a method of adding alloy elements such as Cr and Mo is known. However, in ferritic stainless steel materials, once corrosion (pitting corrosion) has occurred, it progresses faster than in austenitic stainless steel materials, so in order to slow down the rate of corrosion progression, it is necessary to add large amounts of Cr and Mo. However, adding large amounts of Cr and Mo would undermine the advantage of ferritic stainless steel materials, that is, their low cost.
[0005] Furthermore, as a technique for improving the corrosion resistance of ferritic stainless steel materials (raw materials), a method for controlling the amount of added Si is known (for example, Patent Documents 1 to 3). However, improving weather resistance cannot be expected by controlling the amount of Si added. In fact, the addition of Si is effective in improving corrosion resistance in neutral environments, but has almost no effect in inhibiting the progress of corrosion in outdoor environments (especially in low pH environments).
[0006] Furthermore, as a technique for improving the properties of ferritic stainless steel materials, such as corrosion resistance and temper color resistance, it has been proposed to form an oxide film with concentrated Si on the surface of the ferritic stainless steel material (for example, Patent Documents 4 to 6). Such an oxide film with concentrated Si can be formed by adding Si and performing heat treatment in a BA (bright annealing) atmosphere with a low oxygen concentration. [Prior art documents] [Patent documents]
[0007] [Patent Document 1] JP 2018-165384 A [Patent Document 2] JP 2010-229470 A [Patent Document 3] JP 2019-112709 A [Patent Document 4] Japanese Patent Application Publication No. 58-197282 [Patent Document 5] JP 2003-213378 A [Patent Document 6] JP 2008-1945 A Summary of the Invention [Problem to be solved by the invention]
[0008] However, even ferritic stainless steel materials having an oxide film with concentrated Si on the surface cannot be said to have sufficient weather resistance. Regarding the cause of this, a detailed analysis of the oxide film with concentrated Si formed by the conventional method revealed that metal particles such as metallic Fe and metallic Cr with a particle size of several nm were dispersed in the oxide film, and that a Cr-depleted part (hereinafter referred to as "Cr-depleted part") was formed in the surface layer of the material part directly below the metallic particles. This is presumably because the part where abnormal oxidation of the metal occurred in a relatively low temperature range during heat treatment was reduced to metal in a high temperature range. The Cr-depleted part in the surface layer of the material part has low corrosion resistance and does not have a Si-enriched oxide film formed on its surface (metal particles are simply present on the surface), so it is likely to become a corrosion starting point in an outdoor environment, and the desired weather resistance cannot be obtained.
[0009] In addition, the material of ferritic stainless steel may contain inclusions, which act as corrosion initiation points in a corrosive environment, causing a decrease in weather resistance. In particular, if inclusions are present near the surface of the material, they are more likely to dissolve in the corrosive environment, causing gaps to form between the base material of the material and the inclusions. In addition to the driving force of corrosion due to the potential difference with the outside, metal ions (especially Cr ions) eluted by corrosion form hydrates, lowering the pH of the surrounding environment. Ions are less likely to diffuse in the gaps, so pitting corrosion is more likely to progress, and the larger the gap, the more likely the pH in the gap is to decrease.
[0010] The present invention has been made to solve the above-mentioned problems, and an object of the present invention is to provide a ferritic stainless steel material having excellent weather resistance and a method for producing the same. [Means for solving the problem]
[0011] The present inventors have conducted extensive research into ferritic stainless steel materials having an oxide film on a base material, and as a result have found that weather resistance can be improved by controlling the composition of the base material, the number and proportion of specific S-based inclusions, and the Cr concentration in specific regions in addition to the Si concentration of the oxide film. The present inventors have also found that the above-mentioned ferritic stainless steel material can be produced by annealing a ferritic stainless steel material having a prescribed composition under specific conditions. The present invention has been completed under the above-mentioned background.
[0012] That is, the present invention provides a ferritic stainless steel material having a material part and an oxide film formed on the material part, The oxide film has a Si concentration of 30 mass% or more, The material portion contains, by mass, C: 0.100% or less, Si: 1.00 to 3.00%, Mn: 1.00% or less, Ni: 1.00% or less, P: 0.100% or less, S: 0.0020% or less, Cr: 13.00 to 32.00%, N: 0.100% or less, a total of Nb and Ti: 6(C+N) to 0.700%, Cu: 2.00% or less, Mo: 2.50% or less, Al: 0.010 to 0.150%, Ca: 0.0100% or less, Mg: 0.0100% or less, O: 0.004% or less, and the balance being Fe and impurities, and is represented by the following formulas (1) and (2): Al+10Ca+Mg≦0.200 (1) Cr+1.7Si+1.2Mo+0.4(Cu+Ni)>19.0 ···(2) (wherein each element symbol represents the content of each element), In the material, the ratio of the number of S-based inclusions having a diameter equivalent size of 1 μm or more and an S content of 1 mass% or more is 15.0 pieces / mm 2 is as follows: The ferritic stainless steel material has a Cr concentration of 10.0 mass % or more in a region of the material portion directly below the Cr-depleted metal contained in the oxide film.
[0013] The present invention also relates to a steel sheet having, on a mass basis, C: 0.100% or less, Si: 1.00 to 3.00%, Mn: 1.00% or less, Ni: 1.00% or less, P: 0.100% or less, S: 0.0020% or less, Cr: 13.00 to 32.00%, N: 0.100% or less, the total of Nb and Ti: 6(C+N) to 0.700%, Cu: 2.00% or less, Mo: 2.50% or less, Al: 0.010 to 0.150%, Ca: 0.0100% or less, Mg: 0.0100% or less, O: 0.004% or less, with the balance being Fe and impurities, and which satisfies the following formulas (1) and (2): Al+10Ca+Mg≦0.200 (1) Cr+1.7Si+1.2Mo+0.4(Cu+Ni)>19.0 ···(2) (wherein each element symbol represents the content of each element) is annealed at a temperature of 800 to 1000°C for 2.0 minutes or more in an atmosphere with a dew point of -60 to -40°C and an oxygen concentration of 1.0 vol% or less. Effect of the Invention
[0014] According to the present invention, a ferritic stainless steel material having excellent weather resistance and a method for producing the same can be provided. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0015] The following is a detailed description of the embodiments of the present invention. The present invention is not limited to the following embodiments, and it should be understood that modifications and improvements to the following embodiments, which are made based on the ordinary knowledge of those skilled in the art, fall within the scope of the present invention, without departing from the spirit of the present invention. In this specification, the "%" designation for components means "% by mass" unless otherwise specified.
[0016] A ferritic stainless steel material according to an embodiment of the present invention has a material part and an oxide film formed on the material part. Here, in this specification, the term "stainless steel material" refers to a material formed from stainless steel, and the shape of the material is not particularly limited. Examples of the shape of the material include a plate shape (including a strip shape), a rod shape, a tube shape, and the like. In addition, the material may be various shaped steels having a cross-sectional shape such as a T shape or an I shape. In addition, in this specification, "ferritic" means that the metal structure is mainly ferritic phase at room temperature. Therefore, "ferritic" also includes those that contain small amounts of phases other than ferritic phase (e.g., austenite phase, martensite phase, etc.). However, "ferritic" does not include a multi-phase structure of ferritic phase and austenite phase, a multi-phase structure of ferritic phase and martensite phase, or a multi-phase structure of ferritic phase, austenite phase, and martensite phase.
[0017] The material portion has a composition including C: 0.100% or less, Si: 1.00 to 3.00%, Mn: 1.00% or less, Ni: 1.00% or less, P: 0.100% or less, S: 0.0020% or less, Cr: 13.00 to 32.00%, N: 0.100% or less, the sum of Nb and Ti: 6(C+N) to 0.700%, Cu: 2.00% or less, Mo: 2.50% or less, Al: 0.010 to 0.150%, Ca: 0.0100% or less, Mg: 0.0100% or less, O: 0.004% or less, with the balance being Fe and impurities. In this specification, the term "impurities" refers to components that are mixed in due to various factors in raw materials such as ores and scraps and manufacturing processes during industrial production of ferritic stainless steel materials, and are acceptable within a range that does not adversely affect the present invention. For example, impurities include unavoidable impurities. An example of an impurity is O. With regard to the content of each element, "xx% or less" means that the content is xx% or less, but includes an amount exceeding 0% (particularly, exceeding the impurity level).
[0018] If necessary, the material part may further contain one or more selected from Zr: 1.00% or less, Co: 1.00% or less, V: 1.00% or less, W: 1.00% or less, REM: 0.100% or less, Sn: 0.100% or less, and B: 0.0100% or less. Each component will be described in detail below.
[0019] (C: 0.100% or less) C is an element that affects the properties of ferritic stainless steel materials (hereinafter sometimes abbreviated as "stainless steel materials"), such as intergranular corrosion resistance (sensitization suppression effect) and workability. In particular, if the C content is too high, the workability and weather resistance of the stainless steel material will decrease. Therefore, the upper limit of the C content is 0.100%, preferably 0.080%, and more preferably 0.050%. On the other hand, the lower limit of the C content is not particularly limited, but an excessively low C content leads to an increase in refining costs. Therefore, the lower limit of the C content is preferably 0.0001%, more preferably 0.0003%, and even more preferably 0.001%.
[0020] (Si: 1.00~3.00%) Silicon is an element effective in improving the properties of stainless steel materials, such as oxidation resistance, mechanical strength, and weather resistance. From the viewpoint of improving weather resistance (e.g., pitting resistance in a neutral environment such as salt water) among these properties, the lower limit of the silicon content is 1.00%, preferably 1.05%, and more preferably 1.10%. On the other hand, if the silicon content is too high, it acts as a solid solution strengthening element, leading to a decrease in workability and a decrease in weld toughness. Therefore, the upper limit of the silicon content is 3.00%, preferably 2.90%, and more preferably 2.80%.
[0021] (Mn:1.00% or less) Mn is an element effective for fixing S (desulfurization). However, if the Mn content is too high, MnS, which is the starting point of corrosion, is easily generated and the ferrite phase is destabilized. Therefore, the upper limit of the Mn content is 1.00%, preferably 0.80%, and more preferably 0.50%. On the other hand, the lower limit of the Mn content is not particularly limited, but from the viewpoint of obtaining the above-mentioned effect of Mn, it is preferably 0.01%, more preferably 0.02%, and even more preferably 0.05%.
[0022] (Ni: 1.00% or less) Ni is an element effective in improving the weather resistance of stainless steel materials, and has the effect of suppressing the progression of pitting corrosion and crevice corrosion in a low pH environment in particular. However, if the Ni content is too high, the ferrite phase becomes unstable and the manufacturing cost increases. Therefore, the upper limit of the Ni content is 1.00%, preferably 0.80%, and more preferably 0.60%. On the other hand, the lower limit of the Ni content is not particularly limited, but from the viewpoint of obtaining the above-mentioned effect, it is preferably 0.01%, more preferably 0.02%, and even more preferably 0.03%.
[0023] (P:0.100% or less) P is an element that affects the properties of stainless steel materials, such as weldability and workability. However, if the P content is too high, the above properties may be deteriorated, so the upper limit of the P content is 0.100%, preferably 0.080%, and more preferably 0.050%. On the other hand, the lower limit of the P content is not particularly limited, but an excessively low P content leads to an increase in refining costs. Therefore, the lower limit of the P content is preferably 0.001%, more preferably 0.005%, and even more preferably 0.008%.
[0024] (S:0.0020% or less) S is an element that generates S-based inclusions such as MnS, which become the starting point of corrosion, and affects the weather resistance and weld toughness of stainless steel materials. In particular, if the S content is too high, the weather resistance decreases, so it is necessary to reduce the S content and reduce the number of S-based inclusions in the stainless steel material. Therefore, the upper limit of the S content is 0.0020%, preferably 0.0019%, and more preferably 0.0018%. On the other hand, the lower limit of the S content is not particularly limited, but excessively reducing the S content leads to an increase in refining costs. Therefore, the lower limit of the S content is preferably 0.0001%, and more preferably 0.0002%.
[0025] (Cr:13.00~32.00%) Cr is an element effective in improving the corrosion resistance and oxidation resistance of stainless steel materials. In particular, from the viewpoint of ensuring weather resistance in consideration of outdoor salt damage environments, the lower limit of the Cr content is 13.00%, preferably 14.00%, and more preferably 15.00%. On the other hand, if the Cr content is too high, the manufacturing cost increases and it becomes difficult to ensure the toughness of the hot-rolled material, resulting in a decrease in manufacturability. Therefore, the upper limit of the Cr content is 32.00%, preferably 30.00%, and more preferably 25.00%.
[0026] (N:0.100% or less) N is an element that affects the properties of stainless steel materials, such as intergranular corrosion resistance (sensitization suppression effect) and workability. In particular, if the N content is too high, the weather resistance and workability of the stainless steel material are reduced. Therefore, the upper limit of the N content is 0.100%, preferably 0.080%, and more preferably 0.050%. On the other hand, the lower limit of the N content is not particularly limited, but excessively reducing the N content leads to an increase in refining costs. Therefore, the lower limit of the N content is preferably 0.001%, more preferably 0.003%, and even more preferably 0.005%.
[0027] (Total of Nb and Ti: 6(C+N)~0.700%) Nb and Ti are elements that affect the intergranular corrosion resistance (sensitization suppression effect) of stainless steel materials. In addition, since Nb and Ti are elements that are effective in fixing C and N, the total content of Nb and Ti is determined based on the amount of C and N. That is, the lower limit of the total content of Nb and Ti is 6(C+N)% from the viewpoint of obtaining the above-mentioned effect. However, if the total content of Nb and Ti is too high, in addition to increasing the manufacturing cost, the workability and surface quality of the stainless steel material are deteriorated. Therefore, the upper limit of the total content of Nb and Ti is 0.700%, preferably 0.600%, and more preferably 0.500%. In addition, the individual contents of Nb and Ti are not particularly limited, but are each 0.05% or more, preferably 0.06% or more, from the viewpoint of suppressing the coarsening of crystal grains during annealing. In particular, Nb forms carbonitrides such as NbC and NbN, and the pinning effect of these carbonitrides can effectively suppress the coarsening of crystal grains.
[0028] (Cu:2.00% or less) Cu is an element effective in improving the workability and weather resistance of stainless steel materials. In particular, Cu has the effect of suppressing the progress of pitting corrosion in a low pH environment. However, if the Cu content is too high, the ferrite phase becomes unstable and the manufacturing cost increases. Therefore, the upper limit of the Cu content is 2.00%, preferably 1.50%, and more preferably 1.00%. On the other hand, the lower limit of the Cu content is not particularly limited, but is preferably 0.01%, more preferably 0.02%, and even more preferably 0.03%, from the viewpoint of obtaining the effect of Cu.
[0029] (Mo: 2.50% or less) Mo is an element effective in improving the weather resistance and oxidation resistance of stainless steel materials. In particular, Mo has the effect of suppressing the progress of pitting corrosion in a low pH environment. However, if the Mo content is too high, it leads to a decrease in the workability of the stainless steel material and an increase in the manufacturing cost. Therefore, the upper limit of the Mo content is 2.50%, preferably 2.00%, and more preferably 1.50%. On the other hand, the lower limit of the Mo content is not particularly limited, but from the viewpoint of obtaining the effect of Mo, it is preferably 0.01%, more preferably 0.03%, and even more preferably 0.05%.
[0030] (Al: 0.010~0.150%) Al is an extremely effective element as a deoxidizing element. In particular, Al forms oxides together with Si, reducing O (oxygen) in the parent phase. However, if the Al content is too high, the amount of oxides increases, and it is easy to form water-soluble inclusions by combining with sulfides. These inclusions become the starting point of corrosion and reduce the weather resistance of the stainless steel material. They also cause a decrease in the toughness and weldability of the stainless steel material. Therefore, the upper limit of the Al content is 0.150%, preferably 0.130, and more preferably 0.100%. On the other hand, the lower limit of the Al content is 0.010%, preferably 0.015%, and more preferably 0.020%, from the viewpoint of ensuring the deoxidizing effect of Al.
[0031] (Ca:0.0100% or less) Ca is an extremely effective element as a deoxidizing element. In particular, Ca forms oxides together with Si and reduces O (oxygen) in the parent phase. Ca is also an element that improves hot workability and cleanliness of stainless steel materials. However, if the Ca content is too high, oxides and sulfides are easily formed, and in particular, sulfides (CaS) are soluble in water, which can be the starting point of corrosion and reduce the weather resistance of stainless steel materials. Therefore, the upper limit of the Ca content is 0.0100%, preferably 0.0080%, and more preferably 0.0060%. On the other hand, the lower limit of the Ca content is not particularly limited, but from the viewpoint of ensuring the effect of Ca, it is preferably 0.0003%, more preferably 0.0005%, and even more preferably 0.0010%.
[0032] (Mg:0.0100% or less) Mg is an extremely effective element as a deoxidizing element. In particular, Mg forms oxides together with Si and reduces O (oxygen) in the parent phase. Mg is also an element that improves hot workability and cleanliness of stainless steel materials. However, if the Mg content is too high, the manufacturability of stainless steel materials decreases, and the amount of oxides increases, which combine with sulfides to form inclusions soluble in water, which become the starting point of corrosion and reduce the weather resistance of stainless steel materials. Therefore, the upper limit of the Mg content is 0.0100%, preferably 0.0080%, and more preferably 0.0060%. On the other hand, the lower limit of the Mg content is not particularly limited, but is 0.0003%, more preferably 0.0005%, and even more preferably 0.0010%, from the viewpoint of ensuring the effect of Mg.
[0033] (O: 0.004% or less) O forms oxides with other additive elements. When sulfides aggregate on such oxides, they act as water-soluble inclusions that become corrosion initiation sites, leading to a decrease in the weather resistance of the stainless steel material. Therefore, the upper limit of the O content is set to 0.004%, preferably 0.003%, and more preferably 0.002%. On the other hand, an excessive reduction in O leads to an increase in raw material and refining costs, so the lower limit of the O content is preferably 0.0001%, and more preferably 0.0005%.
[0034] (Zr: 1.00% or less, Co: 1.00% or less, V: 1.00% or less, W: 1.00% or less) Zr, Co, V and W are elements effective for improving the oxidation resistance of stainless steel materials. However, if the content of Zr, Co, V and W is too high, the workability and toughness of the stainless steel material will decrease, and the manufacturing cost will increase. Therefore, the upper limit of the content of Zr, Co, V and W is 1.00%, preferably 0.95%, and more preferably 0.90%. On the other hand, the lower limit of the content of Zr, Co, V and W is not particularly limited, but is preferably 0.001%, and more preferably 0.01%.
[0035] (REM: 0.100% or less) REM is an element effective for improving the oxidation resistance of stainless steel materials. However, if the REM content is too high, it leads to an increase in manufacturing costs. Therefore, the upper limit of the REM content is 0.100%, preferably 0.090%, and more preferably 0.080%. On the other hand, the lower limit of the REM content is not particularly limited, but is preferably 0.0001%, more preferably 0.0003%, and even more preferably 0.001%. In addition, REM is a general term for Sc, Y, and lanthanoids, a total of 17 elements, and refers to rare earth metals. Specifically, La, Ce, Nd, etc. can be mentioned, and one of these can be contained alone or two or more can be combined. When two or more rare earth elements are contained, the content of the REM refers to the total content of these rare earth elements.
[0036] (Sn:0.100% or less) Sn is an element effective for improving the oxidation resistance of stainless steel materials. However, if the Sn content is too high, Sn segregates and the manufacturability of stainless steel materials decreases. Therefore, the upper limit of the Sn content is 0.100%, preferably 0.090%, and more preferably 0.080%. On the other hand, the lower limit of the Sn content is not particularly limited, but is preferably 0.001%, and more preferably 0.002%.
[0037] (B:0.0100% or less) B is an element effective for improving the secondary workability of stainless steel materials. However, if the B content is too high, the fatigue strength of the stainless steel material decreases. Therefore, the upper limit of the B content is 0.0100%, preferably 0.0090%, and more preferably 0.0080%. On the other hand, the lower limit of the B content is not particularly limited, but is preferably 0.0001%, and more preferably 0.0003%.
[0038] The material portion satisfies the following formula (1). Al+10Ca+Mg≦0.200 (1) In formula (1), each element symbol represents the content of each element. Formula (1) is related to the proportion of the number of specific S-based inclusions described below, and by satisfying the conditions of formula (1), it becomes easier to reduce the proportion of the number of the specific S-based inclusions. Al, Ca, and Mg used in the calculation based on the element contents in formula (1) are elements related to S-based inclusions formed by the aggregation of S (sulfur) or sulfides. In particular, Al and Mg form oxides, and aggregate with S or sulfides to form S-based inclusions. Ca has a higher tendency to form oxides than Al and Mg, and also a higher tendency to combine with S to form sulfides. As a result of intensive research, it was found that Ca has a 10 times higher tendency to contribute to the formation of S-based inclusions than Al and Mg, and formula (1) was derived.
[0039] The material portion satisfies the following formula (2). Cr+1.7Si+1.2Mo+0.4(Cu+Ni)>19.0 ···(2) In formula (2), each element symbol represents the content of each element. Formula (2) is related to the pitting corrosion resistance of stainless steel materials, and by satisfying the conditions of formula (2), it becomes easier to ensure the weather resistance of stainless steel materials in outdoor environments. In a corrosive environment containing halogen ions such as chloride ions, the oxide film of stainless steel materials may be locally destroyed by these ions, causing pitting corrosion. The occurrence and progression of this pitting corrosion varies greatly depending on the elements contained in the stainless steel material. In general, the pitting corrosion index (PI=Cr+3Mo) based on Cr has been known as an index of the pitting corrosion resistance of stainless steel materials. In this invention, however, it was found that Si, Cu, and Ni have an effect on the progression of pitting corrosion in low pH environments such as crevice environments such as gaps and inside pits, and formula (2) was derived.
[0040] Specifically, we derived equation (2) as follows. First, pitting potential measurement was adopted as a method for easily evaluating the pitting corrosion resistance of stainless steel material, and attention was paid to Cr, Mo, as well as Si, Cu, and Ni contained in stainless steel material, to examine the effects of these elements on the pitting corrosion resistance of stainless steel material. The pitting potential measurement was performed in accordance with JIS G0577:2014, and the current value was 100 μA / cm in a 3.5 mass% NaCl aqueous solution at 30°C. 2 The potential exceeding this limit was defined as the pitting potential V'c100. In the stainless steel material according to the embodiment of the present invention, when the material contains 1.00% or more Si, the pitting potential is improved not only by increasing Cr but also by increasing Si, and the effect is 1.7 times that of Cr. The mechanism that brings about this effect is not necessarily clear, but it is presumed from various analyses that the oxide of Si formed in the oxide film and at the interface of the material part exhibits the effect of suppressing the destruction of the oxide film by halogen ions, especially in a neutral solution environment such as salt water. In addition, when Mo is contained, the effect is 1.2 times that of Cr. Furthermore, when Cu and Ni are contained, the effect is 0.4 times that of Cr. Based on these findings, in the present invention, the calculation formula (2) was derived as Cr+1.7Si+1.2Mo+0.4(Cu+Ni).
[0041] Here, the pitting potential V'c100 of the stainless steel material according to the embodiment of the present invention was compared with the pitting potential V'c100 of SUS430J1L (19Cr ferritic stainless steel material), SUS443J1 (21Cr ferritic stainless steel material), and SUS304 (18Cr-8Ni austenitic stainless steel material). As a result, in the present invention, by making the value of formula (2) exceed 19.0, it was possible to achieve a pitting potential of 0.20V equivalent to SUS430J1L. Also, in the present invention, by making the value of formula (2) 21.0 or more, it was possible to achieve a pitting potential of 0.30V equivalent to SUS443J1 and SUS304. Therefore, in the present invention, the value of formula (2) is set to exceed 19.0. The upper limit of the value of formula (2) is not particularly limited, but if it is too high, the Si content tends to be too high, which increases the tensile strength and hardness, reduces the workability, and increases the manufacturing cost. Similarly, if the Mo, Cu, and Ni contents are high, the raw material cost increases. Therefore, the upper limit of formula (2) is preferably 25.0.
[0042] The material has a diameter equivalent size of 1 μm or more and a S content of 1% or more, and the number ratio of S-based inclusions is 15.0 pieces / mm 2 The following is the result. In this specification, the term "S-based inclusions" refers to inorganic compounds containing S, which are formed during the steelmaking process. S-based inclusions contain sulfides such as MnS and CaS. In addition to sulfides formed alone, S-based inclusions may also be formed by agglomeration of Al, Ca, and Mg oxides together with the sulfides.
[0043] S-based inclusions dissolve in water in a corrosive environment, forming gaps between the base material and the material. A potential difference occurs inside the gap, which not only drives corrosion, but also dissolves metal ions from the material when pitting occurs in the gap. The dissolved Cr ions form hydrates, lowering the pH of the surrounding environment. This tendency is particularly strong in gaps below S-based inclusions, where ion diffusion is difficult, and repassivation is difficult, leading to the progression of pitting. Ferritic stainless steels with low Ni content corrode faster than austenitic stainless steels, so S-based inclusions become corrosion initiation points. It is therefore necessary to reduce the number of S-based inclusions of a specific size that act as corrosion initiation points.
[0044] Among S-based inclusions, S-based inclusions with a diameter equivalent size of 1 μm or more and an S content of 1% or more (hereinafter referred to as "specific S-based inclusions") tend to become corrosion initiation points. Therefore, the number ratio of these specific S-based inclusions is set to 15.0 pieces / mm 2 The corrosion of the base material can be suppressed by controlling the number of specific S-based inclusions below 13.0 pieces / mm. 2 It is preferable that the number of pieces is 10.0 pieces / mm or less.2 It is more preferable that the ratio of the number of the specific S-based inclusions is not particularly limited, since the smaller the ratio, the better.
[0045] The specific S-based inclusion is an S-based inclusion having a diameter equivalent size of 1 μm or more. Here, the "diameter equivalent size" refers to the value obtained by raising the product of the long side dimension and the short side dimension of the shape to the power of 1 / 2 ((long side × short side) 1 / 2 ) This means that even if the shape of the S-based inclusion is irregular, its size can be unambiguously determined. In addition, S-based inclusions with a diameter equivalent size of less than 1 μm are so small that they are unlikely to generate a potential difference between the inside and outside of the gap, which is the driving force for corrosion, and diffusion is likely to occur even when pitting corrosion occurs in the gap. Therefore, since the decrease in pH is only slight, they are unlikely to become the starting point of corrosion. In addition, S-based inclusions with an S content of less than 1% are unlikely to dissolve and form gaps between the base material and the inclusions, and therefore are unlikely to become corrosion initiation points. Therefore, even if S-based inclusions are present in the surface layer of the base material of stainless steel materials, the number ratio of specific S-based inclusions with a diameter equivalent size of 1 μm or more and an S content of 1% or more is set to 15.0 pieces / mm 2 Weather resistance can be improved by the following.
[0046] Here, the number ratio of specific S-based inclusions is measured by polishing the surface of the stainless steel material to remove surface irregularities, mirror-finishing it, and observing it as follows: First, inclusions are detected using an FE-SEM (field emission scanning electron microscope: SU-5000, manufactured by Hitachi High-Tech Corporation) device, and the composition of the specific inclusions is measured by further point-analyzing the parts with an EDX (energy dispersive X-ray analysis) device. Next, among the detected inclusions, the number of specific S-based inclusions having a diameter equivalent size of 1 μm or more and an S content of 1% or more as determined by EDX component analysis is determined. The number of specific S-based inclusions is then divided by the observation area to calculate the number ratio.
[0047] In the material portion, the Cr concentration in the region directly below the Cr-depleted metal contained in the oxide film is 10.0% or more. Here, the term "Cr-poor portion-forming metal" refers to a metal that is a factor in forming Cr-poor portions during annealing in a low-oxygen atmosphere. Examples of Cr-poor portion-forming metals include metallic Cr and metallic Fe. The region of the material part directly below the Cr-poor metal contained in the oxide film is likely to become a "Cr-poor part" lacking in Cr. If the Cr concentration in this region is less than 10.0%, the surface will be in a state where no oxide film is formed (where only metal particles are present on the surface), and this region will easily become a corrosion starting point in an outdoor environment. Therefore, from the viewpoint of preventing this region from becoming a corrosion starting point, the Cr concentration in this region is set to 10.0% or more, preferably 11.0% or more, and more preferably 12.0% or more. The upper limit of this region is not particularly limited, but is typically 30.0%.
[0048] The Cr concentration in the region of the material directly below the Cr-poor metal contained in the oxide film is determined by preparing a sample by exposing the cross section of the stainless steel material in the thickness direction, and then line analyzing the region of the material directly below the Cr-poor metal in the sample using TEM-EDX to determine the mass fractions of Cr, Fe, and Si. The Cr concentration in that region can be calculated using the mass fractions of each element obtained by the following formula (3). Cr concentration in the region [mass%] = Cr mass fraction [mass%] / (Cr mass fraction [mass%] + Fe mass fraction [mass%] + Si mass fraction [mass%]) × 100 (3)
[0049] Next, the oxide film formed on the material portion will be described. The oxide film is an oxide film in which Si is concentrated, and generally contains SiO2. The oxide film may further contain oxides of metals such as Fe, Cr, and Mn. The oxide film has a Si concentration of 30% or more. By controlling the Si concentration within this range, the barrier properties (weather resistance) of the oxide film can be ensured. From the viewpoint of stably ensuring this effect, the Si concentration of the oxide film is preferably 32% or more, and more preferably 35% or more. On the other hand, the upper limit of the Si concentration of the oxide film is not particularly limited, but is typically 60%.
[0050] Here, the Si concentration of the oxide film can be measured using glow discharge optical emission spectroscopy (GD-OES) in accordance with JIS K0144:2018. Specifically, glow discharge optical emission spectroscopy is used to measure the range from the surface to a depth of 1 μm, and in the obtained component concentration profile in the depth direction, the mass fractions of each of the elements Si, Fe, Cr, Mn, and Si are obtained at a depth from the maximum value of the mass fraction of O (oxygen) to a position where it becomes 1 / 4 of the maximum value. Using the obtained mass fractions of each element, the Si concentration of the oxide film can be calculated by the following formula (4). Si concentration in oxide film [mass%] = Si mass fraction [mass%] / (Fe mass fraction [mass%] + Cr mass fraction [mass%] + Mn mass fraction [mass%] + Si mass fraction [mass%]) × 100 (4)
[0051] The ferritic stainless steel material according to the embodiment of the present invention can be produced by annealing a ferritic stainless steel material having the above-mentioned composition at a temperature of 800 to 1000°C for 2.0 minutes or more in an atmosphere with a dew point of -60 to -40°C and an oxygen concentration of 1.0 volume% or less. The annealing may be bright annealing.
[0052] The ferritic stainless steel material is not particularly limited as long as it has the above composition, but is typically a rolled material. As the rolled material, a hot-rolled material, a cold-rolled material, etc. can be used. The rolled material can be produced according to a method known in the art. For example, the cold-rolled material can be produced by melting a ferritic stainless steel having a predetermined composition, hot rolling, annealing, pickling, and then cold rolling. In addition, the rolled material may be subjected to various treatments (annealing, pickling, polishing, etc.) after rolling.
[0053] The dew point during annealing is -60 to -40°C, preferably -55 to -45°C. By controlling the dew point within this range, abnormal oxidation of metal generated in the Cr-depleted portion during heating is easily suppressed, and oxidation of Si is promoted, making it possible to form a desired oxide film. If the dew point is lower than -60°C, the Si concentration in the oxide film is low, making it impossible to obtain the desired weather resistance. Also, if the dew point is higher than -40°C, the Si concentration in the oxide film is low, making it impossible to obtain the desired weather resistance.
[0054] The atmosphere during annealing is a low-oxygen atmosphere with an oxygen concentration of 1.0% by volume or less. The atmosphere may contain an inert gas such as hydrogen gas, nitrogen gas, or argon gas. For example, the atmosphere may be an atmosphere of a single gas of any one of these inert gases, or an atmosphere of a mixed gas of two or more of them. For example, the mixed gas may be a mixed gas containing hydrogen gas and nitrogen gas in a volume ratio of 3:1.
[0055] The heating temperature during annealing is 800 to 1000°C, and the heating time is 2.0 minutes or more. By performing annealing under such conditions, Cr in the material part is diffused, and the Cr concentration of the material part in the region directly below the Cr-poor part-generated metal contained in the oxide film can be increased to 10.0% or more. If the heating time is less than 2.0 minutes, the Cr concentration of the material part in that region cannot be increased to 10.0% or more, and the desired weather resistance cannot be obtained. In addition, if the heating temperature exceeds 1000°C, the crystal grains become coarse and the workability decreases. On the other hand, if the heating temperature is less than 800°C, the thickness of the oxide film becomes insufficient, and the desired weather resistance cannot be obtained.
[0056] The ferritic stainless steel material according to the embodiment of the present invention produced as described above has excellent weather resistance and can be used in various applications where these properties are required, such as building materials such as building panels, piping, etc. EXAMPLES
[0057] The present invention will be described in detail below with reference to examples, but the present invention should not be construed as being limited to these.
[0058] Stainless steel having the composition shown in Table 1 (the balance being Fe and impurities) was melted and hot rolled to obtain a hot rolled sheet having a thickness of 3.0 mm, which was then annealed at 1050°C and pickled to obtain a hot rolled annealed sheet. Next, the hot rolled annealed sheet was cold rolled to obtain a cold rolled sheet having a thickness of 1.0 mm. Next, the cold rolled sheet was annealed under the conditions shown in Table 2 to obtain a ferritic stainless steel sheet. The atmosphere during annealing was a gas atmosphere with an oxygen concentration of 0.01 volume% or less and a hydrogen gas concentration of 99.9 volume% or more. A sample of 300 mm (rolling direction) x 100 mm (width direction) was cut out from the obtained ferritic stainless steel sheet.
[0059] [Table 1]
[0060] [Table 2]
[0061] The samples obtained above were subjected to the following evaluations.
[0062] (Number ratio of specific S-type inclusions) A 10mm x 10mm test piece was cut out from the above sample by cutting. The sample was cut out at a position 20mm or more away from the end in the width direction. Next, resin was filled in so that the surface of the stainless steel plate would be the observation surface, and then it was polished to remove surface irregularities, and finally it was wet polished to a mirror finish. After that, inclusions were detected using an FE-SEM (SU-5000, manufactured by Hitachi High-Tech Corporation) device, and the composition of specific inclusions was measured by EDX point analysis. Note that this measurement was performed using the device's automatic inclusion analysis function, and the conditions are as follows. Measurement range: Measurement area 5mm 2 (2.0mm x 2.5mm) Observation magnification: 200 times (1 visual field range 0.48 mm × 0.64 mm) with 5% overlap, 18 visual fields were measured to obtain the above measurement range. The minimum detectable particle diameter was 0.47 μm. EDX analysis beam diameter: 0.05 μm Among the detected inclusions, the number of specific S-based inclusions with a diameter equivalent size of 1 μm or more and an S content of 1% or more as determined by EDX component analysis was determined. The number of these specific S-based inclusions was divided by the observation area to obtain the number ratio (pieces / mm 2 ) was calculated.
[0063] (Cr concentration in the region of the material directly below the Cr-depleted metal) The above sample was cut into 50 mm squares, and then a measurement specimen with an exposed cross section in the thickness direction was obtained by processing with a focused ion beam (FIB) at an arbitrary position. Next, in the cross section of the measurement specimen, the region of the material part directly below the Cr-depleted part generated metal (metal Cr and metal Fe) was line-analyzed by TEM-EDX to obtain the mass fractions of each element of Cr, Fe, and Si. The observation length in the direction perpendicular to the thickness direction was set to 100 μm or more. Using the obtained mass fractions of each element, the Cr concentration in the region was calculated by the above formula (3).
[0064] (Si concentration in oxide film) A 50 mm square test piece was cut out from the above sample, and the surface was degreased with acetone. Next, a range from the surface of the oxide film to a depth of 1 μm was measured using glow discharge optical emission spectroscopy (GD-OES) in accordance with JIS K0144:2018. The oxide film was analyzed by determining the mass fractions of each of the elements Si, Fe, Cr, Mn, and Si at a depth from the maximum value of the mass fraction of O (oxygen) to a position where it becomes 1 / 4 of the maximum value in the component concentration profile obtained by GD-OES. Then, the Si concentration of the oxide film was calculated by the above formula (1) using the mass fractions of each element obtained.
[0065] (weather resistance) Weather resistance was evaluated by a salt, dry and wet combined cycle test. A test piece of 100 mm (rolling direction) x 50 mm (width direction) was cut out from the above sample, and three sides of the test piece (except one side in the width direction) were covered with resin (one-liquid condensation type RTV rubber KE44 manufactured by Shin-Etsu Chemical Co., Ltd.). Next, two polyethylene tubes of 20 mmφ x 10 mm were bonded onto a Bakelite plate of 70 mm x 150 mm, and the side of the test piece not covered with resin was placed on top of the tubes and bonded. A salt-dry-wet combined cycle test (CCT) was performed on the measurement sample obtained in this way. The sample was placed in a CCT device so that the surface of the test piece for measurement was at 75° to the horizontal plane and the side of the test piece for measurement not covered with resin was at the bottom, and five cycles were performed, each consisting of 5% salt spray (35°C, 2 hours), drying (60°C, 25% RH, 4 hours), and wetting (50°C, 95% RH, 2 hours). The measurement samples were then washed with water and dried, and the rust area ratio on the surface of the test pieces was evaluated (based on JIS G0595:2004). In this evaluation, if the rating number (RN) is 8.0 or higher (corresponding to a rust area ratio of 0.25% or less), it can be determined that the weather resistance is good.
[0066] The above evaluation results are shown in Table 3.
[0067] [Table 3]
[0068] As shown in Table 3, the ferritic stainless steel sheets of Examples 1 to 6 had good weather resistance because the Si concentration of the oxide film, the composition of the base material, the number ratio of specific S-based inclusions, and the Cr concentration in the specific region were all within appropriate ranges. In contrast, the ferritic stainless steel sheet of Comparative Example 1 had an excessively high dew point during annealing, which reduced the Si concentration in the oxide film and resulted in insufficient weather resistance. In the ferritic stainless steel sheet of Comparative Example 2, the dew point during annealing was too low, so the Si concentration in the oxide film was reduced and the weather resistance was insufficient. In the ferritic stainless steel sheet of Comparative Example 3, the heating time during annealing was too short, so that Cr could not be diffused into the specific region (that is, the Cr concentration could not be increased), and the weather resistance was insufficient.
[0069] The ferritic stainless steel sheet of Comparative Example 4 had an excessively high S content, which resulted in a high proportion of specific S-based inclusions and insufficient weather resistance. The ferritic stainless steel sheet of Comparative Example 5 had too high a Ca and Mg content and did not satisfy the condition of formula (1), so the proportion of specific S-based inclusions was high and the weather resistance was insufficient. The ferritic stainless steel sheet of Comparative Example 6 did not satisfy the condition of formula (1), and therefore had a high proportion of specific S-based inclusions, resulting in insufficient weather resistance. The ferritic stainless steel sheet of Comparative Example 7 had an excessively low Al content and an excessively high O content, resulting in a high proportion of specific S-based inclusions and insufficient weather resistance. The ferritic stainless steel sheet of Comparative Example 8 had an excessively low Si content, and therefore the Si concentration in the oxide film was low, resulting in insufficient weather resistance. The ferritic stainless steel sheet of Comparative Example 9 had too little Cr content and did not satisfy the condition of formula (2), so the Cr concentration in the specific region could not be increased and the weather resistance was insufficient.
[0070] As can be seen from the above results, the present invention can provide a ferritic stainless steel material having excellent weather resistance and a method for producing the same.
Claims
1. A ferritic stainless steel material having a material portion and an oxide film formed on the material portion, The oxide film has a Si concentration of 30 mass% or more, The material portion contains, by mass, C: 0.100% or less, Si: 1.00 to 3.00%, Mn: 1.00% or less, Ni: 1.00% or less, P: 0.100% or less, S: 0.0020% or less, Cr: 13.00 to 32.00%, N: 0.100% or less, a total of Nb and Ti: 6(C+N) to 0.700%, Cu: 2.00% or less, Mo: 2.50% or less, Al: 0.010 to 0.150%, Ca: 0.0100% or less, Mg: 0.0100% or less, O: 0.004% or less, with the balance being Fe and impurities, and is represented by the following formulas (1) and (2): Al+10Ca+Mg≦0.200...(1) Cr+1.7Si+1.2Mo+0.4(Cu+Ni)>19.0...(2) (wherein each element symbol represents the content of each element), In the material portion, the number ratio of S-based inclusions having a diameter equivalent size of 1 μm or more and an S content of 1 mass% or more is 15.0 pieces / mm 2 is as follows: A ferritic stainless steel material, in which a Cr concentration in a region of the material portion directly below a Cr-depleted portion-generated metal contained in the oxide film is 10.0 mass % or more.
2. The ferritic stainless steel material according to claim 1, wherein the material portion further contains, by mass, one or more selected from Zr: 1.00% or less, Co: 1.00% or less, V: 1.00% or less, W: 1.00% or less, REM: 0.100% or less, Sn: 0.100% or less, and B: 0.0100% or less.
3. The ferritic stainless steel material according to claim 1 or 2, wherein the Cr-depleted portion-generating metal is metallic Cr and / or metallic Fe.
4. On a mass basis, it contains C: 0.100% or less, Si: 1.00 to 3.00%, Mn: 1.00% or less, Ni: 1.00% or less, P: 0.100% or less, S: 0.0020% or less, Cr: 13.00 to 32.00%, N: 0.100% or less, the total of Nb and Ti: 6(C+N) to 0.700%, Cu: 2.00% or less, Mo: 2.50% or less, Al: 0.010 to 0.150%, Ca: 0.0100% or less, Mg: 0.0100% or less, O: 0.004% or less, the balance being Fe and impurities, and is represented by the following formulas (1) and (2): Al+10Ca+Mg≦0.200...(1) Cr+1.7Si+1.2Mo+0.4(Cu+Ni)>19.0...(2) (wherein each element symbol represents the content of each element) is annealed for 2.0 minutes or more at a temperature of 800 to 1000°C in an atmosphere having a dew point of -60 to -40°C and an oxygen concentration of 1.0 vol% or less.
5. The method for producing a ferritic stainless steel material according to claim 4, wherein the ferritic stainless steel material further contains, by mass, one or more selected from Zr: 1.00% or less, Co: 1.00% or less, V: 1.00% or less, W: 1.00% or less, REM: 0.100% or less, Sn: 0.100% or less, and B: 0.0100% or less.
Citation Information
Patent Citations
Rust-resistant stainless steel and its production
JP1983197282A
Stainless steel annealing-finished material having excellent temper color resistance and production method therefor
JP2003213378A
Bright annealing-finished ferritic stainless steel sheet having excellent rusting resistance and workability and method for producing the same
JP2008001945A
Welded structure made from stainless steel having superior toughness at weld, and stainless steel sheet to be welded
JP2010229470A
Ferritic stainless steel and welded structure
JP2018165384A